Degradation of phorbol esters in jatropha seed cake by pseudomonas aeruginosa DS1 - SHILPI AHLUWALIA; JAI GOPAL SHARMA; PUSHPENDRA SINGH (International Journal of Pharma and Bio Sciences, 2017)
Jatropha curcas is a perennial plant which is widely used as biofuel and is recognized for its medicinal properties. Different parts of Jatropha plant are used for the treatment of human and veterinary diseases. Biodiesel production from Jatropha seed oil results in large amount of residual seed cake which is rich in lignocellulosic compounds, minerals and proteins but presence of certain toxic compounds limits the use of this nutrient rich cake. Phorbol esters are the major toxic compounds found in Jatropha curcas seed cake that make it unsuitable for food and feed applications. Effective utilization of this seed cake necessitates the need of complete removal of its phorbol esters. In this study, we investigated the application of submerged fermentation (SMF) for the detoxification of phorbol esters. SMF was carried out with Jatropha seed cake at 37 ËšC, pH 7, 100 rpm for 9, 12 and 15 h using Pseudomonas aeruginosa DS1. Complete degradation of phorbol esters resulted when the seed cake was fermented for 15 h at 37 ËšC, pH 7, 100 rpm indicating the potential of this process to completely detoxify the Jatropha seed cake in a very short time.